Externalizing and internalizing behavioural problems related to asthma in school children. Issue 11 (12th October 2013) - Annesi‐Maesano, I.; Zhou, C.; Baïz, N.; Banerjee, S.; André Charpin, D.; Caillaud, D.; de Blay, F.; Raherison, C.; Lavaud, F.
Abstract: We investigated the relationships of behavioural problems as assessed using the standardized Strengths and Difficulties Questionnaire (SDQ) to asthma in view of improving asthma management. Six thousand eight hundred and eighty children (mean age 10.4 years, male: 49%) were recruited in the French 6 Cities Study. Children with abnormal or borderline emotional symptoms (internalizing problems) or conduct problems (externalizing problems) were more asthmatic than others ( P < 0.01). Compared to being normal, abnormal emotional symptoms or conduct problems were found to be related to mild‐to‐moderate persistent asthma (logistic model adjusted odds ratio = 1.55 (95% CI = 1.26–1.90) and 1.42 (95% CI = 1.17–1.71), respectively) and to early‐onset asthma (Cox's model Adjusted Hazard Risk = 1.60 (95% CI = 1.27–2.01) and 1.34 (95% CI = 1.05–1.70). Borderline conduct problems were found to be negatively related to parents' knowledge on how to prevent asthma attacks, compared to normal conduct problems [adjusted OR = 0.51 (95% CI = 0.31–0.85)]. Further data are needed to better understand the involvement of behavioural problems in childhood asthma according to phenotypes.